Navigation-Guided Subaxial Cervical Pedicle Screws in Revision Spine Surgery: 2-Dimensional Operative Video. Issue 4 (29th December 2020) - Mao, Jennifer Z; Agyei, Justice O; Ghannam, Moleca M; Khan, Asham; Christensen, Marc; Meyers, Joshua E; Pollina, John; Mullin, Jeffrey P
Abstract: Traditionally, lateral mass screws (LMSs) have been the mainstay of posterior fixation in the subaxial spine. Although LMSs provide adequate fixation, cervical pedicle screws (CPSs) facilitate high fusion rates (90.5%) and provide for greater bone purchase, better reduction, lower rates of screw loosening or pull out, 2 times greater biomechanical advantage, superior stabilization, decreased development of pseudarthrosis, and decreased revision surgeries compared to LMSs. 1-4 In addition, CPSs can be a powerful bail-out option after lateral mass construct failure. Navigation-guided CPS placement has been reported to have an accuracy of 90.3%. 5 Navigation has the added advantage of mitigating screw malposition for the placement of CPS because of the smaller pedicle sizes and variability in cervical anatomy. 1, 3, 6 The potential risks of subaxial CPS placement include the risks of vertebral artery injury, spinal cord injury, and injury to adjacent neurovasculature. 2 The overall radiographic breach rate with intraoperative imaging is reported to range from 2.9% of 22.9%, with the majority of breaches occurring in the lateral direction. 7, 8 Despite radiographic breaches, the occurrence of nerve root injury (0.31% per screw), vertebral artery injury (0.15% per screw), and spinal cord injury (0% per screw) is rare. 3, 7 Here, we demonstrate navigation-assisted C1-C2 posterior fusion, with combined C1 LMSs and C2 pedicle screws with subaxial pedicle screw revision of prior failed instrumentation. 3 The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary.